HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN MOTIVASI MENGAJAR DENGAN KINERJA GURU PPKn SMA NEGERI DI KABUPATEN SOPPENG - Jurana, Jurana (PEP Educational Assessment, 2017)
The research aims at describing the correlation between emotional intelegence and teaching motivation toward PPkn (Civics) teachers’ performance at SMAN (public Senior High Schools) in Soppeng district. This research is an ex-post facto research with causality in nature conducted in 8 public junior high school for 3 months from March to May 2015. This research consists of independent variable (emotional intelligence and teaching motivation) and dependent variable (teachers’ performance). The subjects of this research were all PPKn teachers in Soppeng district. Data was collected by employing quessionnaires. Data was analyzed by employing quantitative descriptive and inferential analysis. The results of the research show that there are positive correlation between emotional intelligence and PPKn teachers’ performance at SMAN in Soppeng district; there are positive correlation between teaching motivation toward PPKn teachers’ performance at SMAN in Soppeng district; there are positive correlation between emotional intelligence and teaching motivation collaboratively toward PPKn teachers’ performance at SMAN in Soppeng district.